Neodomestication and Its Effect on Growth and Production of Wild Yam in Baringo and Uasin Gishu Counties of Kenya - Chemwetich, J. R.; Too, E. J.; Onkware, A. O. (Africa Environmental Review Journal, 2022)
Wild yam (Dioscorea spp.), particularly, Dioscorea schimperiana Kunth tubers have been used as food during times of severe famine. However, there is no documentation on attempted wild yam domestication in Kenya. Therefore, the study was conducted to assess the effect of domestication on growth and production of D. schimperiana, with the aim of developing new yam cultivars to be used to improve food security. Tubers of six (6) D. schimperiana accessions from five (5) selected localities including Kombosang (KB1), Moigutwo (MB1), Mormorio (MB2 and MB2C), Kolol (KE) and Chepsangor (CN) in North Rift region of Kenya were collected. Cultivated yam, Dioscorea alata (MN and MT) accessions obtained from Mathia and Mogoi in Nyeri and Trans-Nzoia Counties respectively, were used as reference. The tubers were sprouted in dark rooms and transplanted in Growth Pouches in the net-house and also in 2 feet holes in the field, spaced at 1m intra row and 1m inter row and staked. Data on internode and vine length, number of leaves, presence or absence of bulbils, number and fresh weight of tubers per plant per accession were recorded. The data collected were then subjected to analysis of variance and the differences among means adopted as significant at P≤0.05. All the five (5) field-grown D. schimperiana accessions significantly showed varied vegetative growth in the net-house and field accessions. The Dioscorea schimperiana produced longer internodes than the D. alata accessions. However, D. alata formed longer vines than the D. schimperiana accessions. Except Dioscorea alata which did not produce tubers in the field but small ones in net-house, D. schimperiana formed single large tubers per plant. Apparently, most D. schimperiana accessions namely, KE, MB1, MB2 and CN produced significantly heavier tubers compared to the control (MB2C), but. KB1 had similar tuber weight as the control. The results show that net-house and field cultivation improve tuber weight of D. schimperiana. Some D. scimperiana (KE, MB1 and CN) showed greater potential for domestication and could be cultivated to improve food security.